﻿A new species of Megalaria (Ramalinaceae, Ascomycota) from Thailand, and recognition of subgenus Catillochroma - Phimpisa Phraphuchamnong; Matthew P. Nelsen; Isabel Distefano; Joel A. Mercado-Diaz; Sittiporn Parnmen; Achariya Rangsiruji; Kawinnat Buaruang; Robert Lücking; H. Thorsten Lumbsch (MycoKeys, 2022)
Tropical regions harbor a substantial diversity of lichenized fungi, but face numerous threats to their persistence, often even before previously unknown species have been described and their evolutionary relationships have been elucidated. Megalaria (Ramalinaceae) is a lichen-forming genus of fungi that produces crustose thalli, and includes a number of lineages occupying tropical rain forests; however, taxonomic and phylogenetic work on this clade is limited. Here we leverage both morphological and sequence data to describe a new species from the tropics, M. pachaylenophila. This taxon forms a crustose thallus, lacks secondary metabolites, and occurs in mangrove forests of Thailand. We supplemented molecular data from this species with data from other species, including two genera related to and occasionally included in Megalaria, namely Catillochroma and Lopezaria. Our analyses revealed Catillochroma species form a monophyletic group embedded within Megalaria, and we therefore recognize this clade at the subgeneric level. Since we only included the type species of Lopezaria in this study, we refrain from proposing a taxonomic conclusion for that clade at the moment. Several taxonomic combinations are made to reflect phylogenetic evidence supporting the inclusion of these species in Megalaria.